2012
DOI: 10.1590/s0004-27492012000400015
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous closure of pediatric traumatic macular hole: case report and spectral-domain OCT follow-up

Abstract: Spontaneous closure of a traumatic macular hole (TMH) is an unusual outcome. Op tical coherence tomography (OCT) and clinical follow-up enabled monitoring of this resolution during a period of a few weeks. We describe a case of spontaneous closure of a TMH with complete visual recovery in a 15 year-old boy and show the follow-up of the macular hole obtained using the Spectral Domain OCT. Keywords

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Vitrectomy is used as the backbone of all treatments with various additional adjuvant techniques suggested as beneficial by different authors. It has been noted that macular holes may spontaneously close in some patients, and therefore a period of watchful waiting has been advised by some [9] . However, at younger ages there is a risk of amblyopia developing due to reduced visual acuity caused by a macular hole [4] , meaning that conservative management even for a short amount of time is not a risk-free strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Vitrectomy is used as the backbone of all treatments with various additional adjuvant techniques suggested as beneficial by different authors. It has been noted that macular holes may spontaneously close in some patients, and therefore a period of watchful waiting has been advised by some [9] . However, at younger ages there is a risk of amblyopia developing due to reduced visual acuity caused by a macular hole [4] , meaning that conservative management even for a short amount of time is not a risk-free strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In the earlier published case reports and case series, absence of intraretinal cysts has not been reported as a factor for closure of macular hole. However, most instances where traumatic macular holes closed spontaneously were not accompanied by intraretinal cysts on OCT 11 12 13 14 15 16 17 18 19 20 21 22 23 , although there are also a few cases with spontaneous closure in the presence of intraretinal cysts 24 25 26 . The presence of intraretinal cysts may be an indicator of internal limiting membrane traction, which may activate Müller cells and cause accumulation of extracellular fluid in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are some reports which deduced that the common feature of cases of spontaneous hole closure was the absence of development of posterior hyaloid detachment [2,9]. Other common features of spontaneously closed TMH cases are young age and smaller hole diameter [2,9,10]. In the case reported herein, there was no posterior hyaloid de-tachment on OCT neither before nor after trauma.…”
Section: Discussionmentioning
confidence: 67%
“…Some authors suggested that the development of epiretinal membranes leads to the contraction of the hole resulting in closure of the hole [6], others suggested RPE and glial cells adjacent to the macular hole proliferated and closed the hole [7], or total posterior hyaloid detachment facilitated hole closure by reducing the anteroposterior tractional forces [8]. On the other hand, there are some reports which deduced that the common feature of cases of spontaneous hole closure was the absence of development of posterior hyaloid detachment [2,9]. Other common features of spontaneously closed TMH cases are young age and smaller hole diameter [2,9,10].…”
Section: Discussionmentioning
confidence: 99%